Cover Feature: Zinc Tetracyanoplatinate: A Reversible Luminescence‐Based Ammonia Sensor (Chem. Eur. J. 38/2019). Issue 38 (22nd May 2019) - Varju, Bryton R.; Wollschlaeger, Sara A.; Leznoff, Daniel B.
Abstract : Ammonia is a common coolant, including in ice skating rinks, but is a hazardous material. ZnPt(CN)4 was shown to exhibit a blue/green luminescence‐based sensory response when exposed to ammonia vapor, as shown in the cover image. The reaction between ZnPt(CN)4 and ammonia is detectable down to 50 ppm of ammonia, and is fully reversible. The reaction involves several species depending on the exposure time and concentration of ammonia, which were characterized using vibrational and luminescence spectroscopy. One of these species, Zn(NH3 )2 Zn(NH3 )3 (Pt(CN)4 )2 has been structurally characterized as a 1D coordination polymer. More information can be found in the Full Paper by D. B. Leznoff et al. on page 9017 .